2011
DOI: 10.1002/dvdy.22701
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of early Xenopus development by the PIAS genes

Abstract: Originally identified as cytokine inhibitors, protein inhibitors of activated STAT (PIAS) are shown to regulate activities of a plethora of proteins and influence diverse processes such as immune response, cancer formation, and cell cycle progression. However, the roles of PIAS during vertebrate embryogenesis are less understood. In this study, we report isolation and initial characterization of all four PIAS genes from Xenopus laevis. The Xenopus PIAS genes are expressed throughout early development and have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…32 Additional cases (showing almost the same phenotype) that either partially overlapped or did not include this 113.5 kb SRO region suggest that part of the phenotypic features could be explained by a 'position effect' or by additional genes close to this SRO (Figure 2). Therefore we hypothesize that the interval from TLE2 to CREB3L3 within 19p13.3, a highly conserved region among different species 33,34 with a rich content in haploinsufficient genes (with 16/55 with a high likelihood of being haploinsufficient), 35 as a critical region responsible for most clinical features. Additional genes that may contribute to clinical features are (from centromere to telomere): EEF2, DAPK3, NMRK2, ATCAY and NFIC, among others (Figure 2), which are involved in cognitive impairment, 36 regulation of myogenic differentiation, 37 apoptosis and transcriptional regulation of canonical Wnt/β-catenin signaling, 38 and autosomal recessive Cayman cerebrallar ataxia, 39 respectively.…”
Section: Genomic Context Deletion Size and Genes Implicatedmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Additional cases (showing almost the same phenotype) that either partially overlapped or did not include this 113.5 kb SRO region suggest that part of the phenotypic features could be explained by a 'position effect' or by additional genes close to this SRO (Figure 2). Therefore we hypothesize that the interval from TLE2 to CREB3L3 within 19p13.3, a highly conserved region among different species 33,34 with a rich content in haploinsufficient genes (with 16/55 with a high likelihood of being haploinsufficient), 35 as a critical region responsible for most clinical features. Additional genes that may contribute to clinical features are (from centromere to telomere): EEF2, DAPK3, NMRK2, ATCAY and NFIC, among others (Figure 2), which are involved in cognitive impairment, 36 regulation of myogenic differentiation, 37 apoptosis and transcriptional regulation of canonical Wnt/β-catenin signaling, 38 and autosomal recessive Cayman cerebrallar ataxia, 39 respectively.…”
Section: Genomic Context Deletion Size and Genes Implicatedmentioning
confidence: 99%
“…The potential relevance of this~1.1 Mb interval from TLE2 to CREB3L3 (that includes the SRO) is supported by its highly conserved nature in all vertebrates, from fish to mammals. 33,34 Further support underlining the importance of this highly conserved region and its contribution to the clinical features in patients with 19p13.3 deletion/duplications is given by their haploinsuffiency (HI) score. HI score (defined by Huang and colleagues, 2010) 35 ranges from 0 to 100, where 0 means highly haploinsufficient and 100 not haploinsufficient.…”
Section: Genomic Context Deletion Size and Genes Implicatedmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact may have a direct relation between PIAS4 and the brain size during the Xenopus embryonic development. 38 We also report here a 16-year-old girl with a PIAS4 nonsense var- and its potential contribution to the phenotype.…”
Section: Disorders Sotos Syndrome (Mim# 117550) In Vivo Experiments Inmentioning
confidence: 81%
“…in vivo experiments in Xenopus demonstrated that PIAS4 is highly expressed in neural cells and neural crest derivatives, including the brain. This fact may have a direct relation between PIAS4 and the brain size during the Xenopus embryonic development …”
Section: Discussionmentioning
confidence: 97%